Investigation of the remote acyl group participation in glycosylation from conformational perspectives by using trichloroacetimidate as the acetyl surrogate. Issue 13 (27th May 2020) - Xu, Ke; Man, Qingmin; Zhang, Yang; Guo, Jia; Liu, Yichu; Fu, Zunyun; Zhu, Yueyue; Li, Yingxia; Zheng, Mingyue; Ding, Ning
Abstract : The remote acyl group participation in glycosylation was studied by using trichloroacetimidate as the acetyl surrogate. The bridging participation intermediates were systematically trapped, and DFT calculations were applied to explain the results. Abstract : Unlike the O 2 neighboring group participation in glycosylation, the participating effect of esters located on more remote positions of glycopyranosyl donors has not been unambiguously established and provokes plenty of questions. Here we systematically trapped the participation intermediates on three common pyranoses based on a 'bis-trichloroacetimidates method', which showed that trichloroacetimidate group participations from O 4 and O 6 are all quite possible except for d -mannopyranosyl O 4. Besides, with the trapped participation intermediates in hand, the NMR data was collected to assist the DFT calculations to build up the most possible participating conformations, which, in turn, predicted the potentials of remote participation by trichloroacetimidates at different positions on the same donor. Finally, the 'tris-trichloroacetimidates method' was employed to support the computational calculations. This work provided a conformational perspective on understanding the potent remote acyl group participation in glycosylation reaction.